Improving Intersection Behavior through Delay-Based Left-Turn Phase Initiation. Issue 1 (January 2014) - Lavrenz, Steven M.; Hainen, Alexander M.; Stevens, Amanda L.; Day, Christopher M.; Li, Howell; Freije, Richard S.; Smith, W. Benjamin; Summers, Hayley; Sturdevant, James R.; Bullock, Darcy M.
Serving protected left-turn phases for one or two vehicles can often be an inefficient use of cycle green time when the opposing through movements are over capacity. This paper assesses the performance of an intersection at which controller logic is applied to delay the call for a protected left-turn phase on the basis of vehicle wait times. During four weeks of evaluation, the delay on left-turn phase calls was varied in 25-s increments from 0 to 75 s. The results indicate that delaying left-turn phase initiation substantially increases the amount of green time for saturated through movements while minimally increasing the travel delay for left-turning drivers. The recommendation is made for agencies to consider using a delay in the range of 25 to 50 s for calling protected phases at intersections at which the opposing through movement is oversaturated and could benefit from additional green time. This paper presents one of the first quantitative studies evaluating potential intersection capacity and performance improvements with respect to left-turn detector delay.